Efficacy of drip irrigation on Melia composita Willd. (Malabar Neem) - JAGANI, A. H.; SHRIVASTAVA, P. K.; LAKKAD, A. P.; THAKUR, N. S.; DWIVEDI, D. K. (Journal of Soil and Water Conservation, 2020)
Irrigation water requirements and irrigation schedules are available for most of the crops grown in different agro climatic regions of the country; however, there is negligible literature on irrigation and water management aspects on forest tree species. Therefore, an experiment was conducted to study the effects of irrigation scheduling and irrigation methods on Melia composita grown in the farm of College of Agricultural Engineering and Technology, Dediapada during year 2017-18. Irrigation schedules of drip irrigation were based on IW/CPE ratio of 0.6, 0.8, 1.0 and 1.2 in the present study. The depth of water applied for the first year was 832 mm, 1109 mm, 1389 mm and 1665 mm barring the rainfall depth and the total time of irrigation was 83, 111, 138 and 169 hours for IW/CPE ratio of 0.6, 0.8, 1.0 and 1.2 IW/ CPE, respectively. The tree height and collar diameter of 4.81 m and 8.27 cm, respectively were found to be statistically significant in IW/CPE = 1.2 while the highest specific leaf weight of 0.34 g/cm2 was found in treatment IW/CPE = 0.6 which was significantly higher than all the other treatments. When the data was extrapolated for 4 years, it was found that the highest and lowest water use efficiency would be 16.32 kg/ha-mm and 14.16 kg/ha-mm under T4 (IW/CPE = 1.2) and T1 (IW/CPE = 0.6) treatments after 4 years while the highest biomass of 154 tonne/ha would be obtained in IW/CPE = 1.20 and the lowest biomass of 99 tonne/ha would be obtained in IW/CPE = 0.6 after 4 years. The highest benefit cost ratio of 9.6 would be obtained in IW/CPE = 1.20 and the lowest benefit cost ratio of 6.7 would be obtained in IW/ CPE = 0.6 after 4 years.